Pemanfaatan Hasil Budidaya Markisa (Passiflora Edulis) Sebagai Inovasi Produk Dari Kelompok Wanita Tani Citra Lestari Kelurahan Karangsari Kecamatan Sukorejo Kota Blitar - Isfia Diana Putri; Zulfa Novita Sari; Natasya Anggraeni; M. Ghulam Dzaki Abdilla; Gideon Setyo Budiwitjaksono; M. Fernanda Abuzar Zuhri (Universitas Kristen Indonesia Toraja, 2023)
KWT Citra Lestari is one of the Women Farmer Groups that owns passion fruit commodities in Karangsari Village, Sukorejo District, Blitar City. The next product that has been done by KWT Citra Lestari members is to make passion fruit into passion fruit syrup. At least processed passion fruit, so new innovations for passion fruit appear. This new innovation aims to foster an entrepreneurial spirit in KWT Citra Lestari and the community. This new innovation is to make processed products from Passion Fruit Jam, where the product is made with natural sugar preservatives. Making passion fruit jam must pay attention to the maturity level of the fruit so that the resulting jam tastes appropriate. The shelf life of passion fruit jam at room temperature and the refrigerator has a different mass.